Green Synthesis Of Butyl Acetate, A Pineapple Flavour Via Lipase-Catalyzed Reaction - S. Mat Radzi; W.A.F. Mustafa; S.S Othman; H.M. Noor (Zenodo, 2011)
Nowadays, butyl acetate, a pineapple flavor has been applied widely in food, beverage, cosmetic and pharmaceutical industries. In this study, Butyl acetate, a flavor ester was successfully synthesized via green synthesis of enzymatic reaction route. Commercial immobilized lipase from Rhizomucor miehei (Lipozyme RMIM) was used as biocatalyst in the esterification reaction between acetic acid and butanol. Various reaction parameters such as reaction time (RT), temperature (T) and amount of enzyme (E) were chosen to optimize the reaction synthesis in solvent-free system. The optimum condition to produce butyl acetate was at reaction time (RT), 18 hours; temperature (T), 37°C and amount of enzyme, 25 % (w/w of total substrate). Analysis of yield showed that at optimum condition, >78 % of butyl acetate was produced. The product was confirmed as butyl acetate from FTIR analysis whereby the presence of an ester group was observed at wavenumber of 1742 cm-1. : {"references": ["P.T. Anastas, L.B. Bartlett, M.M. Kirchhoff and T.0 Williamson, \"The role of catalysis in the design, development and implementation of green chemistry\", Catal. Today, vol. 55, pp. 11-22, 2000", "M. Karra-Chabouni, H. Ghamgui, S. Bezzine, A. Rekik and Y. Gargouri Y, \"Production of flavor esters by immobilized Staphylococcus simulans lipase in a solvent-free system\", J. Process Biochem., vol. 41, pp. 1692-1698, 2006", "R. Ben Salah, H. Ghamghui, N. Miled, H. Mejdoub and Y. Gargouri Y, \"Production of butyl acetate by lipase from novel of Rhizopus oryzae\", J. Biosci. Bioeng., vol. 104, pp. 268-372, 2007", "A. Gilvenc, N. Kapucu and O. Mehmetoglu, \"The production of isoamyl acetate using immobilized lipases in a solvent-free system\", Process Biochem., vol. 38, pp. 379-386, 2002", "S.H. Krishna, S. Divakar, S.G. Prapulla and N.G. Karanth, \"Enzymatic synthesis of isoamyl acetate using immobilized lipase from Rhizomucor miehei\", J. Biotechnol., vol. 87, pp.193-201, 2001", "A.B. Majumder, B. Singh, D. Dutta, S. Sadhukhan and M.N. Gupta, \"Lipase catalyzed synthesis of benzyl acetate in solvent-free medium using vinyl acetate as acyl donor\", Bioorg. Med. Chem. Lett., vol. 16, pp. 4041- 4044, 2006", "R. Sharma, Y. Chisti and U.0 Banerjee, \"Production, purification, characterization, and applications of lipases\", J. Biotechnol. Adv., vol. 19, pp. 627-662, 2001.", "U.T Bornscheuer, \"Enzymes in lipid modification\", eds. Bornscheuer UT, Wiley-VCH, Weinheim, 2000.", "S. Mat Radzi, B. Mahiran B, S. Abu Bakar, A. Arbakariya, M. Rosfarizan, A.R Mohd Basyaruddin and A.R Raja Noor Zaliha, \"High performance enzymatic synthesis of oleyl oleate using immobilized lipase from Candida antartica\", Electron. J. Biotechnol., vol. 83 (3), pp. 292-298, 2005\n[10] G.V. Chowdary and S.G. Prapulla, \"The influence of water activity on the lipase catalysed synthesis of butyl butyrate transesterification\", Process Biochem., vol. 38, pp. 393-397, 2002.\n[11] N. Mat Hadzir, M. Basri, M.B Abdul Rahman, C.N.A Razak, R.N.Z. Abdul Rahman and A.B. Salleh, \"Enzymatic alcoholysis of triolein to produce wax ester\", J. Chem. Technol. Biotechnol., vol. 76, pp.511-515, 2001.\n[12] N.L. Facioli and D. Barrera-Arellano, \"Optimisation of enzymatic esterification of soybean oil deodoriser distillate\", J. Sci Food Agric., vol. 81, pp. 1193-1198, 2001.\n[13] E.L. Soo, A.B. Salleh, M. Basri, R.N.Z. Abdul Rahman and K. Kamaruddin, \"Response surface methodological study on lipase-catalysed synthesis of amino acid surfactants\", Process Biochem., vol. 39, pp. 1511-1518, 2003.\n[14] R. Ben Salah, H. Mosbah, A. Fendi, A. Gargouri, Y. Gargouri and H. Mejdoub, \"Biochemical and molecular characterization of lipase produced by Rhizopus oryzae: a comparative study between n-hexane and solvent-free system\", J Enzym. Microb. Technol., vol. 35, pp.355- 363, 2006.\n[15] M.D. Romero, L. Calvo, C. Alba, M. Habulin, M. Primo2ie and 2. Knez, \"Enzymatic synthesis of isoamyl acetate with immobilized Candida antartica lipase in supercritical carbon dioxide\", Supercritical Fluids, vol. 33, pp.77-84, 2005.\n[16] R. Abdul Rahim, A.B. Salleh, M. Basri and R.N.Z Raja Abd Rahman, \"Palm-based fatty alkanolamides\" in Specialty Esters Alternative Green Synthesis Process, Eds. M. Basri, E.L Soo and A.B Salleh, Universiti Putra Malaysia Press, Serdang, pp 25-39. 2005.\n[17] J.L Kuan, N. Alhindra and J.F Shaw, \"Lipase-catalyzed synthesis of fatty acid diethanolamides\", J Agric. Food. Chem., vol. 49, pp. 5761- 6764, 2001\n[18] C. Torres and C. Otero, \"Part III. Direct enzymatic esterification of rasemic naproxen by lipases in organic solvent\", Enzym, Microb. Technol., vol. 29, pp. 3-12, 2001.\n[19] Z. Idris, E.L Soo, S. Ahmad, M. Basri and R.N.Z Raja Abd Rahman, \"Palm-based fatty esteramines\", in Specialty Esters Alternative Green Synthesis Process, Eds. M. Basri, E.L Soo and A.B Salleh, Universiti Putra Malaysia Press, Serdang, pp 40-53. 2005.\n[20] M.L Foresti and M.L Ferreira, \"Solvent-free ethyl oleate synthesis mediated by lipase from Candida antartica B adsorbed on polypropylene powder\", Catal. Today, vol. 108, pp. 23-30. 2005."]}